(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
In the mosaic of today’s classrooms, diversity reigns supreme. Students bring an array of experiences, cultures, abilities, and learning styles into the educational arena. As educators, it is paramount to embrace these differences and create an environment where every student feels seen, heard, and empowered to thrive. This article explores the concept of inclusive pedagogy—a teaching approach that goes beyond acknowledging diversity and actively seeks to nurture the potential of every individual, fostering a rich and supportive learning environment.